An Analysis of Private Life Insurance Services as Perceived by Life Insurance Buyers in Karnataka - Rajgopal, Mahesh (Indian Journal of Finance, 2015)
Characterized by its large potential and high growth rate, the life insurance industry has been one of the most dynamic sectors, which is playing an increasingly important role in India’s liberalized economy. Since the opening up of the insurance sector for private participation in 2001, there are already 23 private sector life insurance companies with foreign tie-ups operating in India’s life insurance market, along with the public sector giant, Life Insurance Corporation (IRDA Annual Report 2010-11). However, traditionally, life insurance has always been an unsought product in India. These private life insurance companies have found that their market penetration processes are not as smooth as they expected. Without understanding the distinctive insurance investment environment in India and the insurance buyers’ perception towards private life insurance, in particular, the private players are going to face many problems on the way to their goals. The present study attempted to ascertain the significant perceptions of insurance buyers in Karnataka towards private life insurance. Various statistical tools were used to arrive at concrete findings based on which suggestions are offered.